Analysis of the impact of the resources assigned by the National Road Safety Agency for the implementation of the National Road Safety Plan in the department of Atlántico, during the 2016-2020 period (2019)
This document search to determine the effects of the resources that the National Road Safety Agency allocated budget during the 2016-2018 period to the Department of Atlántico to reduce road accidents according to the provisions of the National Road Safety Plan, considering the growing trend of the accidents and mortality due to road accidents affecting the entire Colombian territory. For this, the different concepts related to road safety are explored, to the actors that participate in it directly or indirectly and in the factors that affect it. The method used is quantitative and the sources used are of a secondary type. Finally, it is based on the hypothesis that the results of the National Road Safety Plan have not been positive have not been positive although the decrease in fatalities in recent years. Within the results, it is concluded that the most affected population with road accidents are motorcyclists and people who are in the age range of 20 to 30 years.